The Big Drum ritual of Carriacou : praisesongs in rememory of flight - McDaniel, Lorna (University Press of Florida, 1998)
The Big Drum is the lively ancient dance rite of the small island of Carriacou, Grenada. This book introduces 129 of the ceremonial song texts and dances that call and entertain the ancestors who are central to Carriacou religious experience. McDaniel, who lived in Carriacou at the time of the 1983 invasion of Grenada, frequently observed Big Drum dances and interviewed many "old heads" (wise people) for this book. She concludes it with an analysis of a single calypso that memorializes the invasion and illustrates the history-keeping function of the calypso and Big Drum. She uncovers a structural relationship between ancient praisesongs and modern political songs and suggests the continuing impact of music on the memory of Caribbean people.